Hospitality in Bali after COVID-19: Navigating the Path to Recovery - I Wayan Wijayasa (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
This article examines the impact of the COVID-19 pandemic on Bali's hospitality industry and explores strategies for its recovery. The study analyzes the economic, social, and environmental consequences of the pandemic on Bali's tourism sector. It investigates coping strategies and resilience measures implemented by industry stakeholders to overcome the challenges. The role of sustainable tourism practices in the resilience and recovery of Bali's hospitality industry is also examined. The article offers insights into the post-pandemic transformation of the guest experience, emphasizing the adoption of technology-driven solutions, personalized services, and cultural immersion. Additionally, it highlights the importance of balancing sustainability and growth in rebuilding Bali's tourism sector. This research contributes to the understanding of the challenges faced by Bali's hospitality industry after COVID-19 and provides recommendations for its sustainable recovery.